New records of the mites Geckobia bataviensis Vitzthum, 1926 and Pterygosoma dracoensis Jack, 1962 (Trombidiformes: Pterygosomatidae) from Timor-Leste - Jacinavicius, Fernando de C.; Bassini-Silva, Ricardo; Oda, Fabrício H.; Kaiser, Hinrich (Entomological Communications, 2021)
We report on the presence of scale mites (Trombidiformes: Pterygosomatidae) parasitizing three species of lizards in Timor-Leste. Geckobia bataviensis Vitzthum, 1926 was found associated with the Common House Gecko, Hemidactylus frenatus Duméril & Bibron, 1836, and the Indopacific Tree Gecko, Hemiphyllodactylus typus Bleeker, 1860, whereas Pterygosoma dracoensis Jack, 1962 was found on the patagia of a Timor Flying Dragon, Draco timoriensis Kuhl, 1820. The association of G. bataviensis with H. frenatus was well documented previously, but this is the first properly documented record of this mite for Timor-Leste. Our report of G. bataviensis on H. typus is the first association of this mite with this gecko. This is the second report of P. dracoensis on D. timoriensis and the first for Timor-Leste.